Investigation of the Binding Interaction of α-amylase with Chrysophyllum albidum Seed Extract and its Silver Nanoparticles: A Multi-Spectroscopic Approach - Alfred, Moses Oladele (Chemical Data Collections, Elsevier, 2020)
The interactions between α-amylase, one of the key enzymes linked with postprandial glucose regulation, and Chrysophyllum albidum seed methanolic extract(CSME) and its greensynthesized silver anoparticles(CSAgNP) were investigated using multiple spectroscopy including Fourier Transform-Infrared(FT-IR), ultraviolet(UV)-visible absorption, fluorescence spectroscopy, and biochemical analysis. FT-IR spectroscopy revealed presence of some functional groups in the samples. CSME and CSAgNP inhibited α-amylase. The intrinsic fluorescence intensity of α-amylase was quenched by CSME and CSAgNP via static mechanisms, indicating formation of complex between the enzyme and inhibitors. α-AmylaseCSAgNP complex had higher binding constants. The binding processes were exothermic, entropy driven, spontaneous, and involved hydrogen bonds and van der Waals force. Synchronous fluorescence quenching indicated alteration in microenvironment of α-amylase catalytic site tyrosine residues.FT-IR spectroscopy revealed shifts in amide I peak position of α-amylase due to interaction with CSME/CSAgNP. Absorption spectroscopy also affirmed changes in enzyme conformation. This study may provide theoretical basis for designing novel α-amylase inhibitors.
Keywords: Chrysophyllum albidum; Silver nanoparticles; α-Amylase inhibition; Protein-ligand binding interaction; Fluorescence quenching; Spectroscopy